2011
DOI: 10.1158/1078-0432.ccr-10-2762
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapy of VEGFR2 and EGFR Significantly Inhibits Growth of Anaplastic Thyroid Cancer in an Orthotopic Murine Model

Abstract: Purpose: Anaplastic thyroid carcinoma (ATC) is one of the most lethal human cancers with a median survival of 6 months. The inhibition of epidermal growth factor receptor (EGFR) alone, or with VEGF receptor 2 (VEGFR2), represents an attractive approach for treatment of ATC. Several reports have examined agents that target these receptors. However, with the misidentification of as many as 60% of all commonly used ATC cell lines, the significance of these past findings is unclear.Experimental Design: Cell lines … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 43 publications
5
58
0
1
Order By: Relevance
“…Gule and colleagues (16) reported that the antitumor effects of vandetanib were mediated through inhibition of VEGF signaling and antiangiogenesis rather than through direct antiproliferative effects on tumor cells. In our in vivo study, vandetanib dose dependently suppressed the phosphorylation of VEGFR-2 and microvascular development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gule and colleagues (16) reported that the antitumor effects of vandetanib were mediated through inhibition of VEGF signaling and antiangiogenesis rather than through direct antiproliferative effects on tumor cells. In our in vivo study, vandetanib dose dependently suppressed the phosphorylation of VEGFR-2 and microvascular development.…”
Section: Discussionmentioning
confidence: 99%
“…Vandetanib (Zactima; ZD6474) is an orally bioavailable, small-molecule VEGFR-tyrosine kinase inhibitor with additional activity against EGFR-tyrosine kinase and RET receptor tyrosine kinase (16). Therefore, vandetanib, in addition to inhibiting endothelial cell proliferation through the blockade of VEGF-induced signaling, can suppress tumor cell growth more directly through the blockade of EGFR autocrine signaling (17).…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 Analysis of variance of the maximum linear slope value SS max of three rabbit groups 2, 4, and 6 weeks after surgery (Mean±SD) (%/s). a indicates significant differences between groups A and C, P < 0.05; b indicates significant differences between groups A and B, P < 0.05; and c indicates significant differences between groups B and C, P < 0.05. ture of a tissue or tumor [6][7][8][9][10][11][12][13], such as microvasculature perfusion and capillary permeability, and mean transit time [Several compartmental models could also be used to fit these data (e.g., the bi-exponential Brix model), of them one could calculate the area under the curve (IAUC) as another measurement]. Nowadays, DCE-MRI is commonly used to assess bone graft viability [14,15].…”
Section: Perfusion Assessment Via Dce-mrimentioning
confidence: 99%
“…This is thought to be due to an 'off target' effect of pazopanib on inhibition of Aurora A kinase, a critical step in mitotic cell spindle formation, stabilization and separation during cell cycle [12]. RET and RET/PTC targeted agents (sorafenib, sunitinib, vandetanib) have also shown some success [13][14][15][16][17].…”
mentioning
confidence: 99%